Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 4 - Calculating the Derivative - 4.3 The Chain Rule - 4.3 Exercises: 7

Answer

$f(g(x))= \dfrac{3}{4}x-\dfrac{55}{8}$ $g(f(x))=\dfrac{3}{4}x+41$

Work Step by Step

Substitute g(x) in f(x): $f(g(x))= \dfrac{6x-1}{8}+7=\dfrac{3}{4}x-\dfrac{55}{8}$ Substitute f(x) in g(x): $g(f(x))= 6(\dfrac{x}{8}+7)-1=\dfrac{3}{4}x+41$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.